CRITICAL THINKING IN HIGHER EDUCATION: WHY UNIVERSITIES MUST MOVE BEYOND MEMORISATION (Ustozlar uchun, 2026)
Universities around the world claim to produce graduates who think independently, reason carefully, and solve problems creatively. In practice, however, the teaching methods dominant in many higher education institutions still reward students who reproduce information accurately over those who question it thoughtfully (Brookfield, 2012; Nilson, 2016). This article argues that critical thinking — understood as the disciplined ability to examine assumptions, weigh evidence, and reach well-reasoned conclusions — is not something that emerges automatically from years of university study (Facione, 1990). It must be deliberately cultivated through purposeful instructional design, assessments that demand reasoning rather than recall, and a classroom culture that treats uncertainty as intellectually productive rather than threatening (Bean, 2011; Mezirow, 1990). Drawing on a range of contemporary educational research, this article explores what critical thinking genuinely involves at the university level, why so many students arrive in higher education without it, and what specific changes in teaching, assessment, and institutional culture could make a meaningful difference (Halpern, 2014; Paul & Elder, 2019). The discussion is grounded in practical examples and concludes with a set of recommendations intended to be useful to students, instructors, and academic administrators alike (Tsui, 2002).